Exploring linguistics landscapes in Depok City Square Park - Supriatnoko Supriatnoko (International Journal Labs, 2024)
This research aims to explore the language use and cultural symbols in public spaces in Depok City Square Park, West Java Province. The research raised the issue of language signs and cultural symbols in Depok City Square Park. This research uses a qualitative approach. It uses the observation method through photography techniques. The photo taken serves as image data. Photos are classified into five taxonomies of Spolsky and Cooper (1991) signs, namely road signs, advertising signs, information signs, warning and prohibition signs, and warning signs. Data were analyzed using a Linguistic Landscapes approach. From the data analysis, the conclusion is obtained: Depok City Square Parks is open: Tuesday to Friday at 07.00 am-17.00 pm. Saturday and Sunday at 06.00 am to 18.00 pm, the park equips a children’s playgound, BMX Area, sports fields and park benches. The language signs displayed in the park area are in the form of writing and text accompanied by pictures. Writing words, phrases and sentences complies with Indonesian language rules; The Depok City Government conveyed messages to visitors in the form of warnings and prohibitons. Linguistic Landscapes tends to use monolingual Indonesian. Betawi cultural symbols can be found in the area of this park called Gigi Balang.